The Apple of Discord - Walcott, Earle Ashley, 1859-1931; Stephens, Alice Barber, 1858-1932 (Salt Lake City, UT : Project Gutenberg, 2016)
"The Apple of Discord" by Earle Ashley Walcott is a novel written in the early 20th century. The story revolves around a fierce feud between two influential families, the Kendricks and the Boltons, in a developing San Francisco. The narrative follows Hampden, a fledgling attorney, who becomes embroiled in the conflict as he is drawn into secretive dealings and power struggles involving both families. The opening of the novel introduces Colonel Wharton Kendrick, who seeks the help of Hampden to investigate the activities of his rival, Peter Bolton. The chapter sets the stage for a complicated web of intrigue, betrayal, and violence as Kendrick suspects Bolton may be plotting against him. As Hampden embarks on this secretive task, he experiences an immediate threat to his life from a mysterious attacker, ultimately revealing the tensions of the familial feud that will unfold throughout the story. The narrative cleverly mixes elements of personal drama, law, and socio-political commentary, hinting at a rich exploration of character motivations and deeper societal themes. (This is an automatically generated summary.)
Release date is 2016-05-28
Produced by Al Haines
Keywords: San Francisco (Calif.) -- Fiction